2007
DOI: 10.1142/s0129183107009480
|View full text |Cite
|
Sign up to set email alerts
|

Discovered Function for Positron Collisions With Alkali-Metal Atoms Using Genetic Programming

Abstract: Genetic programming (GP) has been used to discover the function that describes the collisions of positrons with sodium, potassium, rubidium and cesium atoms at low and intermediate energies. The GP has been running based on experimental data of the total collisional cross sections to produce the total cross sections for each target atom. The incident energy and the static dipole polarizability of the alkali target atom have been used as input variables to find the discovered function. The experimental, calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…We notice that our GTB model calculations give an improvement upon the theoretical models. Also, in comparison with our previous work (Genetic Programming model [15,16]) we have found that the GTB model gives best fitting in very short computational time (0.73 sec).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…We notice that our GTB model calculations give an improvement upon the theoretical models. Also, in comparison with our previous work (Genetic Programming model [15,16]) we have found that the GTB model gives best fitting in very short computational time (0.73 sec).…”
Section: Resultssupporting
confidence: 53%
“…Recently, there are a number of machine learning techniques such as neural networks and genetic programming [13][14][15][16][17][18][19][20][21][22] used to predict and model the total cross sections. The reason for applying machine learning methods (based on statistical learning theory or biological inspired techniques, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…AI techniques are becoming very useful as alternate approaches to conventional ones (Whiteson & Whiteson 2009). Within AI, genetic programming (GP) is a global optimization algorithm and an automatic programming technique that has been applied in physics and astrophysics (Cohen et al 2003, El-Bakry & Radi 2007, Teodorescu & Sherwood 2008, El-dahshan 2009, Schmidt & Lipson 2009, Indranil et al 2013. GP is a powerful tool that can be used to solve complex fitting problems.…”
Section: Optimization Approachmentioning
confidence: 99%
“…Recently, several modelling methods based on soft computing systems include the application of artificial intelligence (AI) techniques. These evolution algorithms have a physically powerful existence in this field [15][16][17][18][19]. The behavior of p-p and pb-pb interactions are complicated due to the non-linear relationship between the interaction parameters and the output.…”
Section: Introductionmentioning
confidence: 99%